2021
DOI: 10.1021/acsapm.1c00825
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating Polymer Network of Rubbery Epoxy and Glassy PMMA: Network Inhomogeneities and Dynamic Heterogeneities

Abstract: Interpenetrating polymer networks (IPN) are model polymeric systems for vibration damping applications owing to their unique viscoelastic properties. They are characterized by presence of static frozen inhomogeneities at molecular scale and are dynamically heterogeneous at a segmental level. These fundamental and characteristic features of IPNs need to be characterized in order to deduce their structure–macroscopic property correlations. In the present study, we report sequential IPNs prepared from a polyether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…From Figure a, an unusually broad tan δ peak encompassing a temperature range from −80 to 170 °C is observed, resembling the loss factor profiles of interpenetrating polymer networks (IPNs) . The broad tan δ profile of the networks is characterized by discernible peaks at −25 and 108–110 °C, with a broad interphase connecting the two segmental relaxation peaks.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…From Figure a, an unusually broad tan δ peak encompassing a temperature range from −80 to 170 °C is observed, resembling the loss factor profiles of interpenetrating polymer networks (IPNs) . The broad tan δ profile of the networks is characterized by discernible peaks at −25 and 108–110 °C, with a broad interphase connecting the two segmental relaxation peaks.…”
Section: Resultsmentioning
confidence: 90%
“…From Figure 3a, an unusually broad tan δ peak encompassing a temperature range from −80 to 170 °C is observed, resembling the loss factor profiles of interpenetrating polymer networks (IPNs). 46 The broad tan δ profile of the networks is characterized by discernible peaks at −25 and 108−110 °C, with a broad interphase connecting the two segmental relaxation peaks. A continuum of relaxation times pertaining to the relaxation of HTPB, PPG, and polyol SS as well as extensively H-bonded HS domains could be the genesis of this broad tan δ peak.…”
Section: Resultsmentioning
confidence: 99%
“…19 However, most of the studies on VEMs reported in the literature pertain to their evaluation of loss factors from DMA. [20][21][22][23] Reports on their analysis at the system level (CLD or FLD) representing the real-time scenario of their application is rather scanty. [24][25][26] Prediction of vibration damping can be carried out using either closed-form solutions or the finite element method (FEM) with the aid of commercial software for numerical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, various kinds of methods have been used to increase the toughness of the epoxy resin. A great deal of reports show that the introduction of soft phases such as elastomers, core–shell particles, block copolymers, and interpenetrating networks into the epoxy matrix can greatly improve the toughness. However, the incorporation of the soft phases will lead to the decrease of the glass transition temperature ( T g ) or mechanical properties such as strength, modulus, stiffness, and so on. , Besides, it was also demonstrated that the uniform distribution of rigid particles , in the epoxy matrix can overcome the disadvantages of using soft toughening agents by improving the toughness without sacrificing mechanical properties or T g .…”
Section: Introductionmentioning
confidence: 99%
“…1 In past decades, various kinds of methods have been used to increase the toughness of the epoxy resin. A great deal of reports show that the introduction of soft phases such as elastomers, 2 core−shell particles, 3 block copolymers, 4 and interpenetrating networks 5 into the epoxy matrix can greatly improve the toughness. However, the incorporation of the soft phases will lead to the decrease of the glass transition temperature (T g ) or mechanical properties such as strength, modulus, stiffness, and so on.…”
Section: ■ Introductionmentioning
confidence: 99%